2020
DOI: 10.1113/ep088017
|View full text |Cite
|
Sign up to set email alerts
|

Multivesicular body and exosome pathway responses to acute exercise

Abstract: New Findings What is the central question of this study?What is the impact of acute aerobic and aerobic + resistance (concurrent) exercise on the regulation of multivesicular body formation in human skeletal muscle? What is the main finding and its importance?Gene expression for proteins associated with multivesicular body biogenesis was increased in response to concurrent exercise, and gene expression of microRNA processing (genetic information) was increased in response to aerobic and concurrent exercise. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…The observations by Lovett et al (2018) are supported by ELV protein expression studies following a non-damaging, combined exercise intervention (Garner et al, 2020). Participants performed a bout of acute aerobic (45 min of two-legged cycle ergometry at 55% of VO 2max ) or combined exercise (aerobic bout followed by single leg knee extensor exercise at 55% of the 1-RM workload until volitional fatigue), and performing skeletal muscle biopsies from the vastus lateralis of healthy young men (Garner et al, 2020). In comparing pre-to 1 h post-exercise, Garner et al (2020) observed no changes in the protein expression of Alix, TSG101 or CD63 in the vastus lateralis following either exercise protocols.…”
Section: Effects Of Other Exercise Modalitiesmentioning
confidence: 68%
See 2 more Smart Citations
“…The observations by Lovett et al (2018) are supported by ELV protein expression studies following a non-damaging, combined exercise intervention (Garner et al, 2020). Participants performed a bout of acute aerobic (45 min of two-legged cycle ergometry at 55% of VO 2max ) or combined exercise (aerobic bout followed by single leg knee extensor exercise at 55% of the 1-RM workload until volitional fatigue), and performing skeletal muscle biopsies from the vastus lateralis of healthy young men (Garner et al, 2020). In comparing pre-to 1 h post-exercise, Garner et al (2020) observed no changes in the protein expression of Alix, TSG101 or CD63 in the vastus lateralis following either exercise protocols.…”
Section: Effects Of Other Exercise Modalitiesmentioning
confidence: 68%
“…Despite evidence of muscle damage (i.e., a ∼5-fold increase in creatine kinase activity from Pre-to 24 h post exercise), there was no evidence of an increase in ELV number or size at either the 2 or 24 h post-exercise timepoints. The observations by Lovett et al (2018) are supported by ELV protein expression studies following a non-damaging, combined exercise intervention (Garner et al, 2020). Participants performed a bout of acute aerobic (45 min of two-legged cycle ergometry at 55% of VO 2max ) or combined exercise (aerobic bout followed by single leg knee extensor exercise at 55% of the 1-RM workload until volitional fatigue), and performing skeletal muscle biopsies from the vastus lateralis of healthy young men (Garner et al, 2020).…”
Section: Effects Of Other Exercise Modalitiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Emerging evidence suggests that exercise enhances the biogenesis of MVBs and exosomes (Garner et al, 2020). Subsequently, the release of exosomes following exercise carries exerkines to mediates intercellular communication (Y.…”
mentioning
confidence: 99%
“…Emerging evidence suggests that exercise enhances the biogenesis of MVBs and the resulting exosomes (Garner et al, 2020). Subsequently, exosome release following exercise can carry exerkines that might modulate intercellular communication (Safdar and Tarnopolsky, 2018).…”
Section: Skeletal Muscle Exosomesmentioning
confidence: 99%